Choosing architects for competitions - experiences from the selection of design teams in Sweden - Magnus Rönn (FORMakademisk, 2014)
This article presents results from a study of prequalification in architectural competitions. The aim is to develop knowledge of how the organizer appoints candidates to restricted competitions in Sweden. Prequalification is a selection procedure used early in the competition process to identify suitable candidates for the following design phase. The overall research question in the study is about how organizers identify architects / design teams. The methodology includes an inventory of competitions, case studies, document review and interviews of key-persons. Ten municipal and governmental competitions have been examined in the study. The invitation emerges during negotiation at the organizing body. General conditions, submission requirements and criteria for the evaluation of applications by architect firms are part of an established practice. All clients have an assessment procedure made up of two distinct stages. First they check whether applications meet the specific "must requirements" in the invitation. Thereafter follows an evaluative assessment of the candidate's professional profile, which is based on the criteria in the invitation. Reference projects and information from the referees are important sources of information in this stage. Decisive in the final assessment is the organizer's perception of the candidates' ability to produce projects of architectural quality, the ability to combine creative solutions with functional requirements and aptitude to work with developers and contractors.